New Heavy-Duty Sampling System for Hydrogen Refuelling Stations—Comparison of Impact of Light-Duty Versus Heavy-Duty Sampling Techniques on Hydrogen Fuel Quality - Linga Reddy Enakonda; Thomas Bacquart; Shirin Khaki; Fangyu Zhang; Hannah Kerr; Benjamin Longhurst; Abigail S. O. Morris (Hydrogen, 2025)
The hydrogen fuel quality is critical to the efficiency and longevity of fuel cell electric vehicles (FCEVs), with ISO 14687:2019 grade D establishing stringent impurity limits. This study compared two different sampling techniques for assessing the hydrogen fuel quality, focusing on the National Physical Laboratory hydrogen direct sampling apparatus (NPL DirSAM) from a 35 MPa heavy-duty (HD) dispenser and qualitizer sampling from a 70 MPa light-duty (LD) nozzle, both of which were deployed on the same day at a local hydrogen refuelling station (HRS). The collected samples were analysed as per the ISO 14687:2019 contaminants using the NPL H2-quality laboratory. The NPL DirSAM was able to sample an HD HRS, demonstrating the ability to realise such sampling on an HD nozzle. The comparison of the LD (H2 Qualitizer sampling) and HD (NPL DirSAM) devices showed good agreement but significant variation, especially for sulphur compounds, non-methane hydrocarbons and carbon dioxide. These variations may be related to the HRS difference between the LD and HD devices (e.g., flow path, refuelling conditions and precooling for light duty versus no precooling for heavy duty). Further study of HD and LD H2 fuel at HRSs is needed for a better understanding.